2014
DOI: 10.1007/s10584-014-1172-6
|View full text |Cite
|
Sign up to set email alerts
|

Downscaling reveals diverse effects of anthropogenic climate warming on the potential for local environments to support malaria transmission

Abstract: The potential impact of climate warming on patterns of malaria transmission has been the subject of keen scientific and policy debate. Standard climate models (GCMs) characterize climate change at relatively coarse spatial and temporal scales. However, malaria parasites and the mosquito vectors respond to diurnal variations in conditions at very local scales. Here we bridge this gap by downscaling a series of GCMs to provide high-resolution temperature data for four different sites and show that although outpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…S2 610) and do not require long-term climate change to be relevant, yet few studies consider such effects. We also demonstrate important differences between vector species in thermal sensitivity of life history traits and overall vector competence, cautioning against the use of mixed-species data and extrapolation across vector-parasite pairings, which is a common feature of many studies exploring environmental influences on transmission27928.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…S2 610) and do not require long-term climate change to be relevant, yet few studies consider such effects. We also demonstrate important differences between vector species in thermal sensitivity of life history traits and overall vector competence, cautioning against the use of mixed-species data and extrapolation across vector-parasite pairings, which is a common feature of many studies exploring environmental influences on transmission27928.…”
mentioning
confidence: 85%
“…This non-linearity means that small changes in environmental temperature can lead to large changes in transmission risk. Recent evidence suggests that malaria incidence is increasing in cooler regions of the world due to global warming345678. However, the effects of environmental change on malaria transmission are potentially complex5679, and the implications for malaria risk in optimum transmission settings remain poorly defined.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…have done regional projections of vector-borne disease transmission. To examine the consequences of using downscaled versus global climate models on predictions of future malarial incidence, Paaijmans et al compared results from raw global circulation models to downscaled models and found that the raw models may underestimate transmission of P. falciparum by as much as threefold in hot and 12-fold in cold extremes [20].…”
Section: All Over the Map?mentioning
confidence: 99%
“…Most statistical and mechanistic models used to predict mosquito borne disease transmission incorporate climate drivers of disease transmission by utilizing environmental data collected from general circulation weather models 1,2932 , down-scaled weather data 33 , outdoor weather stations 34,35 , or remotely sensed land surface temperature data 36–38 . While working with these data is methodologically tractable, mosquitoes do not experience environmental variation at such coarse scales 39,40 .…”
Section: Introductionmentioning
confidence: 99%